New Syllabus mathematics workbook 1 (8th edition) - Har Ban,Yeap; Joseph B.W Yeo; Choy Ban Heng (Karachi: Oxford university press, 2024)
The New Syllabus Mathematics workbook 1 (8th Edition) is an essential resource for students beginning their study of mathematics. It provides comprehensive coverage of fundamental topics such as numbers, algebra, geometry, and data handling, ensuring a solid mathematical foundation.
The New Syllabus Mathematics workbook 1 (8th Edition) is a key educational resource tailored for students beginning their journey in mathematics. This edition is designed to build a strong foundational understanding of mathematical concepts, promoting both theoretical knowledge and practical application.
Keywords: Numbers; Data Handling